2020
DOI: 10.1590/1518-8345.4604.3360
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the use and reuse of face masks among Brazilian individuals during the COVID-19 pandemic

Abstract: Objective to identify the factors associated with the use and reuse of masks among Brazilian individuals in the context of the COVID-19 pandemic. Method cross-sectional study conducted in the five Brazilian regions, among adult individuals, via an electronic form disseminated in social media, addressing general information and the use of masks. Bivariate analysis and binary logistic regression were used to identify the factors associated with the use and reuse of masks. Results 3,981 (100%) individuals pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
4
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 15 publications
2
32
4
3
Order By: Relevance
“…A cross-sectional study enrolling 3981 non-healthcare workers in Brazil found that 71.1% of individuals reused masks during the COVID-19 pandemic and that women were less likely to reuse masks than men [24]. Another cross-sectional descriptive study involving 1000 adults in Hong Kong found that 35.4% of the subjects reused face masks during the COVID-19 pandemic, and individuals with inadequate face masks were more likely to reuse masks [25].…”
Section: Factors Associated With Reuse Of Masksmentioning
confidence: 99%
“…A cross-sectional study enrolling 3981 non-healthcare workers in Brazil found that 71.1% of individuals reused masks during the COVID-19 pandemic and that women were less likely to reuse masks than men [24]. Another cross-sectional descriptive study involving 1000 adults in Hong Kong found that 35.4% of the subjects reused face masks during the COVID-19 pandemic, and individuals with inadequate face masks were more likely to reuse masks [25].…”
Section: Factors Associated With Reuse Of Masksmentioning
confidence: 99%
“…Outra medida adotada nos centros de hemodiálise consiste no uso obrigatório de máscara pelos pacientes desde a saída de casa (18)(19) , bem como pelos profissionais e acompanhantes, quando presentes (10,19,20,22,23,27,29) . As máscaras são barreiras mecânicas para a prevenção da dispersão de gotículas, om a finalidade de autoproteção contra as doenças, e também para prevenir a transmissão de patógenos entre os indivíduos doentes e os saudáveis, as máscaras têm sido utilizadas como uma intervenção popular de saúde pública (32) .…”
Section: Discussionunclassified
“…In Brazil, 55.8% of adult face mask users reuse face masks, among which 27.2% reuse a face mask for one to two times [ 16 ]. In Hong Kong, 54% of adult face mask users reuse face masks, among which 83.3% reuse a single face mask for one to two times [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As much as 77.7% of the adults in Brazil use fabric/cotton homemade masks exclusively or in combination with other types of mask, such as surgical masks, N95 masks, and paper or gauze masks. Only 27.8% of the adults use face masks exclusively [ 16 ]. In Hong Kong, however, homemade masks are not recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation